KEBIJAKAN PENDIDIKAN RESPONSIF GENDER - suryanef suryanef (Kafa`ah: Journal of Gender Studies, 2013)
The policies of a school tend to be no gender value and no a wise  affirmation applied to the broadening  of women's access to continuing education to a higher level or go on to university. The efforts made by the community, school, or government for the extend of women's access to secondary education remains piecemeal. For that we need the synergy in developing strategic policies involving tripartite, where the role of local government as a policy initiator. Keywords : Gender-responsive education policies, expanding access, womenCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i2.60